Computer Control at Lockenby Universal Plate Mill - B. Hall; R. Shepherd (Measurement + Control, 1969)
The AEI CON PAC 4060 Computer at Dorman Long's Lackenby Plate Mill has been installed to provide a control system aimed at producing an accurate control of the thickness of hot rolled plate, together with maximizing the mill throughput without exceeding the mechanical or electrical constraints of the mill. This project is running late, partly because a major change to the function of the mill was created when a 4-stand continuous mill was built last year, requiring the Universal Mill to operate sometimes as a reversing rougher and sometimes as a finishing mill, and partly because of instrumentation difficulties. The addition of a second furnace and other plant changes has necessarily required modification to be made to the control. Although the whole project is unfinished a number of functions have been working on-line for the past two years. Our experience connected with developing an on-line system working 24 hours a day on a live mill provides the background against which this general paper has been written. The fully adaptive control is expected to be operating in August, 1969.